Pengaruh Profitabilitas, Leverage, dan Likuiditas terhadap CSR Disclosure - Vianinnda Ayang Dipasti; Erna Sulistyowati (Ekonomis: Journal of Economics and Business, 2022)
Corporate Social Responsibility (CSR) is a corporate social responsibility program for the impact of the company's operations which are the company's ethical actions. CSR programs are mandatory, but cases of low CSR disclosure are still common. The purpose of this study was to examine and measure the effect of profitability, leverage, and liquidity on CSR disclosure. This type of research is quantitative research with associative method. The population of this study is the Consumer Non-Cyclicals Food & Beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Determination of the sample using purposive sampling method. The number of samples is 21 companies. The amount of data studied is 105 data in the form of annual reports of sample companies. Multiple linear regression analysis technique with SPSS version 25 was used in this study. The results of this study indicate that liquidity has an effect on CSR disclosure, while profitability and leverage have no effect on CSR disclosure.